Workshop Komunikasi: “Duduk Bacarita” - Raja Syarief Harahap; Deassy J. A. Hehanussa; Winda Yuniar; Nani Rumbia (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
The "Duduk Bacarita" Communication Workshop was organized as a response to the need for effective interpersonal communication to strengthen social cohesion in the multicultural society of Maluku. This program aims to improve participants' skills in managing misunderstandings, resolving disagreements, and enhancing emotional regulation through an approach rooted in local culture. The workshop was held in Dusun Kotania Bawah over two sessions, using lecture, demonstration, and interactive discussion methods, followed by Bacarita practice sessions as an egalitarian dialogue model. Observations showed improvements in participants' communication behavior, such as the courage to express opinions, active listening skills, and empathy in conversations. Additionally, interactions among participants became more fluid and inclusive in accordance with the principles of Bacarita, which emphasize respect for others' opinions and feelings. These findings support social dialogue theory and demonstrate that a culturally rooted approach, such as Bacarita, is effective in improving interpersonal communication. The success of this workshop indicates that local traditions can be a relevant strategy for conflict prevention and strengthening social cohesion in community empowerment programs. The workshop proves that local culture, when applied to communication, can foster more harmonious relationships in diverse communities.